Changes in Funeral Music Practices of Vietnamese People in the Northern Delta, Vietnam - Lam, Nguyen Dinh (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
The funeral music of the Vietnamese people in the Northern Delta represents unique type of traditional musical heritage practiced and passed down by many generations of Vietnamese people to this day. Vietnamese people often say: “Sống dầu đèn, chết kèn trống” (If you live with lamp oil, die with trumpets and drums) - meaning that the sound of drums and trumpets at the funeral of the dead is like fire and oil in human life. However, this unique artistic heritage is facing a risk of change, as many traditional qualities in this type of music are gradually hybridizing and disappearing. The main research method of this study is qualitative research, focusing on in-depth interviews with elite artisans - elderly people with good memories and the ability to excel in practicing funeral music. In-depth interviews are done with artisans in families who have practiced and taught funeral music for generations. Research results show that the funeral music of Vietnamese people in the Northern Delta has changed quite a lot compared to tradition; Modern compositions songs are gradually being practiced in the Vietnamese funeral space here. The main reason is that the local cultural heritage management and preservation policy, for many years, was not given much attention. At the same time, pragmatic economic factors resulting from these artisans practicing this heritage in the face of the impact of the new economic context of society - are also the central cause of this transformation. The need to preserve this precious heritage in the cultural and social life of contemporary Vietnamese people is also an issue discussed in this study.